2013
DOI: 10.1111/pcmr.12105
|View full text |Cite
|
Sign up to set email alerts
|

Decreased regulatory T‐cells and CD4+/CD8+ ratio correlate with disease onset and progression in patients with generalized vitiligo

Abstract: The aim of present study was to evaluate CD4(+) /CD8(+) ratio and CD4(+) CD25(hi) FoxP3(+) Tregs in GV patients with reference to their effect on disease onset and progression. Flow cytometry was used for determination of CD4(+) /CD8(+) ratio and Tregs in 82 patients and 50 controls. CD8(+) T-cell counts were significantly higher in GV patients as compared with controls (p = 0.003). Active GV patients showed higher CD8(+) T-cell counts compared with stable GV patients (p = 0.001). The CD4(+) /CD8(+) ratio decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
107
4
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 134 publications
(138 citation statements)
references
References 29 publications
14
107
4
6
Order By: Relevance
“…Such alterations might lead to the higher levels and activation of cytotoxic T cells (Fig. 1) which have been reported in individuals with the disease [10,11]. Currently, however, studies examining any reciprocal relationship between CD4 + CD25 + FoxP3 + Tregs and CD8 + in vitiligo progression are lacking.…”
Section: Regulatory T Cells In Vitiligomentioning
confidence: 97%
See 4 more Smart Citations
“…Such alterations might lead to the higher levels and activation of cytotoxic T cells (Fig. 1) which have been reported in individuals with the disease [10,11]. Currently, however, studies examining any reciprocal relationship between CD4 + CD25 + FoxP3 + Tregs and CD8 + in vitiligo progression are lacking.…”
Section: Regulatory T Cells In Vitiligomentioning
confidence: 97%
“…More recently, repigmentation in a mouse model of spontaneous epidermal depigmentation was found to be accompanied by an increased Treg cell infiltration, suggesting their importance in preventing an ongoing immune response against melanocytes [17]. To date, several studies have indicated perturbations in Treg cell numbers and/or function in vitiligo patients [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Such alterations might lead to the higher levels and activation of cytotoxic T cells (Fig.…”
Section: Regulatory T Cells In Vitiligomentioning
confidence: 99%
See 3 more Smart Citations